Kesesuaian Lahan untuk Tanaman Hortikultura pada Areal Bekas Hutan Rawa Gambut di Kabupaten Nagan Raya Provinsi Aceh - Khairil Anwar; Sufardi Sufardi; Helmi Helmi (Jurnal Floratek, 2016)
Land Suitability for Horticultural Crops on Areal of Ex-Peat Swamp Forest of Nagan Raya Districts, Aceh Province Abstract. The conversion of peat swamp forests into farmlands can potentially change the soil’s characteristics and morphology, which in turn will affect land suitability. This research was performed to assess the land suitability level for the development of horticultural crops in a former peat swamp forest area which covers an area of 2732,12 ha in Darul Makmur Sub-district, Nagan Raya Regency, Aceh Province. The research was conducted using the descriptive method through ground surveys and laboratory analyses. The land suitability for horticultural crops evaluation was accomplished using the FAO criteria, which is matching between the land criteria and growing requirements for each horticultural crop. The evaluated lands were grouped into five homogeneous land units (HLU). The results indicated that every former peat swamp forest that has been converted into farmland had a land suitability level of S3, wa (marginally suitable) for several horticultural crops, such as pineapples, melons, eggplants, tomatoes, spinaches, red chili peppers, cucumbers, long beans, and watermelons. The main limitation factors were high rainfall and nutrients retention. The results also showed that mustard greens and shallots had a land suitability level of N (not suitable) because of the high rainfall.